2016
DOI: 10.1523/jneurosci.0220-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of Cellular Proliferative Activity in Brain Neurogenic Regions in Rats under Depression and Treatment by Enhanced [18F]FLT-PET Imaging

Abstract: Neural stem cells in two neurogenic regions, the subventricular zone and the subgranular zone (SGZ) of the hippocampal dentate gyrus, can divide and produce new neurons throughout life. Hippocampal neurogenesis is related to emotions, including depression/anxiety, and the therapeutic effects of antidepressants, as well as learning and memory. The establishment of in vivo imaging for proliferative activity of neural stem cells in the SGZ might be used to diagnose depression and to monitor the therapeutic effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Hippocampal neurogenesis is involved in limbic functions, including regulation of emotion, depression and anxiety, as well as therapeutic effects of antidepressants (Bettio et al, ; Cameron & Glover, ; Hyer et al, ; Tamura et al, ). Studies have demonstrated that decreased neurogenesis may be one cause of depression (Tamura et al, ). Indeed, many antidepressants have been shown to stimulate adult hippocampal neurogenesis (Brooker et al, ).…”
Section: Functional Aspects Of New Dgcs In the Adult Hippocampusmentioning
confidence: 99%
“…Hippocampal neurogenesis is involved in limbic functions, including regulation of emotion, depression and anxiety, as well as therapeutic effects of antidepressants (Bettio et al, ; Cameron & Glover, ; Hyer et al, ; Tamura et al, ). Studies have demonstrated that decreased neurogenesis may be one cause of depression (Tamura et al, ). Indeed, many antidepressants have been shown to stimulate adult hippocampal neurogenesis (Brooker et al, ).…”
Section: Functional Aspects Of New Dgcs In the Adult Hippocampusmentioning
confidence: 99%
“…Recently, we succeeded in establishing quantitative PET imaging methods for evaluating neurogenic activity in the adult brain with probenecid, a drug transporter inhibitor at the blood-brain barrier (BBB). 22 Probenecid is an inhibitor of ATP-binding cassette (ABC) transporter subfamily C members (ABCCs) and solute carrier proteins, such as organic anion transporter 3 (OAT3). [23][24][25] The current study has encouraged us to establish PET imaging for proliferative activity in the hippocampus of adult primates, including monkey and human, with [ 18 F]FLT and probenecid.…”
mentioning
confidence: 99%
“…[23][24][25] The current study has encouraged us to establish PET imaging for proliferative activity in the hippocampus of adult primates, including monkey and human, with [ 18 F]FLT and probenecid. 22 There are some differences in adult neurogenesis between rodents and primates. Indeed, the number of newborn neurons in primates appears to be several times lower than that in rodents.…”
mentioning
confidence: 99%
See 2 more Smart Citations